Coordenação do ciclo celular e inibição da desacetilação no desenvolvimento de embriões suínos produzidos por transferência nuclear - Rissi, Vitor Braga (2015)
Somatic cell nuclear transfer (SCNT) has been used in recent years for various purposes; to produce copies of genetically superior animals or genetically modified animals. Mainly as a research tool, trying to understand aspects related to cell reprogramming. Despite past several years since birth first animal cloned from a somatic cell, the efficiency remains low. The causes are multifactorial and may involve species particularities, the cell used as nuclear donor or enucleated cytoplasts. Currently it is known that the main problem found in cloned embryos is related to an incomplete cellular reprogramming, which in turn compromises the expression of genes required for normal embryonic development. In the present work we studied different cell cycle associations between cytoplasts (oocytes) and donor cells and its relation with a histone deacetylase inhibitor on the reprogramming of pig embryos produced by SCNT. Oocytes were enucleated at MII or TII (pre-activated) and the associated with previously synchronized cells in G1/G0 and G2/M phase of the cell cycle using or not a histone deacetylase inhibitor Scriptaid in the first hours of embryo culture. The results showed cell cycle incompatibilities between TII cytoplasts and G1/G0 cells even as MII cytoplasts G2/M cells regarding cell reprogramming. Scriptaid treatment showed a cell cycle dependent effect, since the improvement in embryo development was observed when using MII cytoplasts, regardless of the cell used as the donor nucleus. Although widely used in order to improve cell reprogramming in cloned embryos, it was demonstrated the relationship between inhibition of deacetylation with cell cycle interactions between and cytoplasts donor cells on the development of pig embryos produced by SCNT.